Behavioural assessment of Potamotrygon stingrays under different food enrichment strategies - Gonzaga, Cassia Regina Ramos; de Azevedo, Cristiano Schetini; Colbachini, Helen; Reisfeld, Laura Chrispim; Padilha, Fabiana Lúcia André; Gutierrez, Rafael Caprioli; Pizzutto, Cristiane Schilbach (Frontiers in Ethology, 2026)
IntroductionFreshwater stingrays of the genus Potamotrygon are endemic to South America and increasingly maintained in aquaria worldwide, yet welfare studies on these species remain limited. Environmental enrichment, particularly feeding strategies, is recognised as stimulating natural behaviours and improving welfare in captivity.MethodsThis study assessed the behavioural responses of Potamotrygon motoro, P. orbignyi, and P. falkneri to three feeding methods designed to impose different levels of access difficulty: (i) scattered food at the surface (easy), (ii) food buried in the substrate (intermediate), and (iii) food placed inside perforated bottles (difficult). Research was conducted at the São Paulo Aquarium, where eight adult females were housed in a mixed-species tank. Over three weeks, behaviours were recorded using scan sampling at 45-second intervals and analysed using Generalised Linear and Generalised Linear Mixed Models.ResultsStingrays spent significantly more time interacting with food under all enrichment treatments than under standard feeding, and exhibited reduced inactivity and increased swimming. Enriched conditions elicited species-typical behaviours such as substrate disturbance during foraging.DiscussionOverall, the findings demonstrate that feeding challenges, as they align with elasmobranch behavioural ecology, promote behavioural diversity and indicators of improved welfare. Incorporating such enrichment into routine husbandry may enhance the quality of life in captive stingrays and provide evidence-based guidance for welfare practices in aquaria and zoological institutions.